Retrospective observational case-control study comparing prehospital thrombolytic therapy for ST-elevation myocardial infarction with in-hospital thrombolytic therapy for patients from same area. Issue 8 (26th July 2005) - Chittari, M S V M; Ahmad, I; Chambers, B; Knight, F; Scriven, A; Pitcher, D
Abstract : Objectives: To compare a system of prehospital thrombolytic therapy, delivered by paramedics under medical guidance, with in-hospital thrombolytic therapy in meeting National Service Framework (NSF) targets for treatment of acute myocardial infarction at a District General Hospital setting in England. Design: Retrospective observational case-control study comparing patients with suspected acute myocardial infarction (AMI) treated with thrombolytic therapy in the prehospital environment with patients treated in hospital. Setting: Wyre Forest District and Worcestershire Royal Hospital, UK. Participants: (A) All patients who received prehospital thrombolytic therapy for suspected AMI accompanied by electrocardiographic features considered diagnostic. (B) Patients who received thrombolytic therapy after arrival at hospital for the same indication, matched with group A by age, gender and postcode. Main outcome measures: 1. Call to needle time 2. Percentage of patients treated within one hour of calling for medical help 3. Appropriateness of thrombolytic therapy 4. Safety of thrombolytic therapy Results: 1. The median call to needle time for patients treated before arriving in hospital (n = 27) was 40 minutes with an inter-quartile range 25–112 (mean 43 minutes). Patients from the same area who were treated in hospital (n = 27) had a median time of 106 minutes with an inter-quartile range 50–285 (mean 126 minutes). This represents a median time saved by prehospital treatment of 66 minutes. 2. 60 minutes after medical contact, 96 % of patients treated before arrival in hospital had received thrombolytic therapy; this compares with 4% of patients from similar areas treated in hospital. 3. Myocardial infarction was confirmed in 92% (25/27) of patients who received prehospital thrombolytic therapy and similarly 92% (25/27) of those given in-hospital thrombolytic therapy. 4. No major bleeding occurred in either group. Group A suffered fewer in-hospital deaths than group B (1 versus 4). Cardiogenic shock (3 patients) and ventricular arrhythmia (5 patients) were seen only in group B. Conclusion: Paramedic-delivered thrombolytic therapy can be delivered appropriately, safely, and effectively. Time gains are substantial and can meet the national targets for early thrombolytic therapy in the majority of patients.